Cure of chronic hepatitis C virus infection after DAA treatment only partially restores the functional capacity of exhausted T cell subsets: a systematic review - Apol, Ása Didriksen; Sølund, Christina; Vinten, Caroline; Underwood, Alexander P.; Bukh, Jens; Weis, Nina (Frontiers in Immunology, 2025)
IntroductionChronic hepatitis C virus (HCV) infection drives T cells into a dysfunctional state due to persistent antigen exposure. This state persists despite viral clearance with previously used interferon-based treatments. Treatment exclusively with direct-acting antivirals (DAAs), introduced in 2014, has revolutionised HCV treatment with cure rates exceeding 95%. This systematic review investigates whether HCV cure by DAA treatment restores the functional capacity of different exhausted T cell subsets.MethodsWe systematically searched the databases PubMed and Embase on June 26th, 2024, for studies assessing T cell exhaustion post-cure by DAA treatment. Eligibility criteria included interferon-free DAA treatment of adult patients with chronic HCV infection, with no co-infection with hepatitis B virus (HBV) or human immunodeficiency virus (HIV). Studies meeting all inclusion and no exclusion criteria were eligible for full-text screening, and only studies presenting original data were included.ResultsThe search identified a total of 448 articles, with 35 articles eligible for full-text screening. Among these, 26 met the inclusion criteria and were included in this systematic review. A total of 919 individuals with chronic HCV infection were included. Following HCV cure, most T cell subsets showed only partial restoration of function. Notably, advanced stages of fibrosis were associated with sustained exhaustion across multiple T cell subsets.ConclusionsThis systematic review found that exhausted T cell subsets are only partially restored after HCV cure by DAA treatment. Severe fibrosis, which can be considered a proxy for the duration of infection, appears to impede the reversal of the immune dysfunction. Further studies are warranted to better understand the influence of potential confounders such as age, sex, fibrosis stage, and duration of infection on the restoration of immune function to gain essential insights for future research.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024540474.